2002
DOI: 10.1103/physreve.65.036210
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar organization of Gavrilov-Silnikov-Newhouse sinks

Abstract: The numerical analyses of the Hénon map suggest the following features. As we increase the value of the control parameter around each stable period of the period-1 branch, an infinitely large series of period n-tupled saddle nodes appears in the following sequence (nϭ . . . ,5,4,3). The limit of each series is the infinitely large set of homoclinic points, created at the homoclinic tangency for the respective flip saddle ͑boundary saddle in the case of period 1͒. These observations are in good agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The sequence of global bifurcations uncovered in §5 is actually almost identical to that following the saddle node bifurcation to period-1 cycles in that map (Grebogi et al 1987;Goswami & Basu 2002). We did not investigate the question but it cannot be ruled out the closure of W u (U B 1 ) is a Hénon-type attractor in a limited range of Rm.…”
Section: Connections With Other Chaotic Systems and Hydrodynamic Tranmentioning
confidence: 84%
“…The sequence of global bifurcations uncovered in §5 is actually almost identical to that following the saddle node bifurcation to period-1 cycles in that map (Grebogi et al 1987;Goswami & Basu 2002). We did not investigate the question but it cannot be ruled out the closure of W u (U B 1 ) is a Hénon-type attractor in a limited range of Rm.…”
Section: Connections With Other Chaotic Systems and Hydrodynamic Tranmentioning
confidence: 84%
“…, N, we let ξ ij denote the (i, j)-element of Ξ and χ i = e T i χ. Assumption (4), which states that f Y 0 does not map E u x X 0 to E s x X 0 , implies that e T 1 g Y 0 (ae 1 ) is nonzero for some a ∈ R. But e T 1 g Y 0 (a 0 e 1 ) = 0 because y 0 = h −1 (a 0 e 1 ) maps to E s x X 0 under f Y and y 0 ∈ Σ. By (7.52), we have e T 1 g Y 0 (ae 1 ) = ξ 11 a + χ 1 .…”
Section: Proof Of Theorem 51mentioning
confidence: 99%
“…The single-round periodic solutions can be asymptotically stable, but sufficiently close to a non-degenerate homoclinic tangency, asymptotically stable single-round periodic solutions do not coexist. Other invariant sets exist near homoclinic tangencies, such as multi-round periodic solutions, and indeed the complete bifurcation structure is fractal [4]. Attractors may coexist, and infinitely many attractors coexist on parameter sets known as Newhouse regions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In [9] it was shown that smooth maps exhibit infinitely many attractors on a dense set of parameter values (known as a Newhouse region) near where the map has a homoclinic tangency. Typically the related bifurcation structure is extremely complex involving nested bifurcation sequences [10,8]. Area-preserving maps may exhibit infinitely many elliptic periodic orbits [11].…”
Section: Introductionmentioning
confidence: 99%